Coeur en santé St-Henri--a heart health promotion programme in Montreal, Canada: design and methods for evaluation. Issue 5 (October 1995) - O'Loughlin, J; Paradis, G; Kishchuk, N; Gray-Donald, K; Renaud, L; Finès, P; Barnett, T
Abstract : STUDY OBJECTIVE--This paper describes the objectives, design, and methods of evaluation of the impact of the coeur en santé St-Henri programme, as well as selected results from the evaluation to date. It discusses the possible effects of study design choices made to maintain the impact evaluation within budget. DESIGN--The impact of the programme is evaluated in a community trial which compares the prevalence of cardiovascular disease behavioural risk factors before and after programme implementation in the intervention and a matched comparison community, in both longitudinal cohort and independent sample surveys. In addition, repeated independent sample surveys are conducted in the intervention community to monitor awareness of and participation in the programme. PARTICIPANTS--The baseline sample for both the longitudinal cohort and independent sample surveys included 849 subjects from the intervention community (79.3% of 1071 eligible subjects--8.0% could not be contacted and 12.6% refused) and 825 subjects from the comparison community (77.8% of 1066 eligible subjects--6.6% could not be contacted and 15.6% refused). The two surveys on awareness and participation conducted to date, included 461 (71.0% of 649 eligible subjects) and 387 (67.9% of 570 eligible subjects) subjects respectively from the intervention community. MEASUREMENTS--Baseline data for the longitudinal cohort and independent sample surveys on behavioural risk factor outcomes including use of tobacco, physical activity behaviour, high fat diet, and behaviours related to blood pressure and cholesterol control were collected in 35 minute telephone interviews in both the intervention and comparison communities. Data on awareness of and participation in the programme were collected in 10 minute interviews in the intervention community only in two independent sample surveys conducted seven and 22 months respectively after the baseline survey. RESULTS--With the exception of smoking, the intervention and comparison communities were similar at baseline with regard to the prevalence of behavioural risk factors studied. Awareness of the coeur en santé programme increased from 64.1% in January 1993 to 72.9% 15 months later. Participation in the programme increased from 21.3% to 33.7%. CONCLUSIONS--This paper presents background information on the evaluation of the impact of the coeur en santé programme, as a reference for future publications.